TRANSLATION TECHNIQUES OF CULTURAL WORDS APPLIED IN THE NOVEL THE HUNGER GAMES - Yasminda Dilisayana; Fatchul Mu'in; Nasrullah Nasrullah (Intensive Journal, 2023)
To translate a book into other languages requires sufficient knowledge. It cannot just randomly  be translated, because readers may have difficulty understanding the content. It is important to know and understand the techniques of translation before translating to avoid making mistakes. Before translating a book, translator should know and understand some translation techniques. The researcher conducted this study to find translation techniques which were applied by the translator in translating cultural words in the novel The Hunger Games by Suzanne Collins. This research used descriptive qualitative research. The source of the data is The Hunger Games novel written by Suzanne Collins and its Indonesian version that is translated by Hetih Rusli. The research instrument in this study is the researcher herself with the help of table list. The researcher considered to focus on cultural words in the novel as a necessary data and analyzed the translation techniques based on the theory by Molina and Albir. The result of this research showed that there are twelve translation techniques which were applied by the translator in translating 84 cultural words found in the novel. There are 29 calque, 19 Borrowing, 13 Amplification, 6 Linguistic compression, 2 Description, 5 Discursive creation, 3 Linguistic amplification , 2 Literal translation, 2 Particularization, 1 Established equivalent, 1 Generalization, and 1 Reduction. The researcher offers that the reason why the translator mostly used calque technique is because most of the cultural words in The Hunger Games novel have the equivalent in Indonesian.